Recent Acquisition of Functional m6A RNA Demethylase Domain in Orchid Ty3/Gypsy Elements - Alvarado-Marchena, Luis; Martínez-Pérez, Mireya; Aparicio, Frederic; Pallas, Vicente; Maumus, Florian (Frontiers in Plant Science, 2022)
• Long terminal repeats (LTR) retrotransposons are transposable elements (TEs) representing major components of most plant genomes. The fixation of additional conserved protein domains in their genomes is considered a rare event in the course of their evolution. Such changes can bring novel functions and increase their fitness by playing a role in the regulation of their replicative cycle or by affecting their integration landscape so that the detection of new domains can in turn reveal important aspects of host-TE interactions. • We have mined angiosperm genomes for the presence of additional domains in LTR retrotransposons. • We report a lineage of large (25 kbp) Gypsy-type elements in the genomes of Phalaenopsis orchids that contain an additional open reading frame containing a 2-ODD domain with close affinity to those responsible for m6A RNA demethylase activity in AlkB proteins. By performing in vitro assays, we demonstrate the RNA binding capability and the demethylase activity of the Gypsy-encoded AlkB protein, suggesting it could be functional against cognate TE mRNA in planta. • In line with recent literature, we propose that the fixation of an RNA demethylase in this lineage of LTR retrotransposons may reflect an important role for epitranscriptomic control in host surveillance against TEs.